2016
DOI: 10.1158/0008-5472.can-15-1790
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Fusion Genes in Testicular Germ Cell Tumors

Abstract: Testicular germ cell tumors (TGCT) are the most frequently diagnosed solid tumors in young men ages 15 to 44 years. Embryonal carcinomas (EC) comprise a subset of TGCTs that exhibit pluripotent characteristics similar to embryonic stem (ES) cells, but the genetic drivers underlying malignant transformation of ECs are unknown. To elucidate the abnormal genetic events potentially contributing to TGCT malignancy, such as the existence of fusion genes or aberrant fusion transcript expression, we performed RNA sequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 38 publications
5
27
0
Order By: Relevance
“…These findings support our previous results that showed that RCC1-ABHD12B expression, but not CLEC6A-CLEC4D expression, was significantly reduced when a pluripotent embryonal carcinoma cell line (NTERA2) was differentiated in vitro (14). These observations support a biological significance of these fusion transcripts being markers of pluripotent TGCTs.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings support our previous results that showed that RCC1-ABHD12B expression, but not CLEC6A-CLEC4D expression, was significantly reduced when a pluripotent embryonal carcinoma cell line (NTERA2) was differentiated in vitro (14). These observations support a biological significance of these fusion transcripts being markers of pluripotent TGCTs.…”
Section: Discussionsupporting
confidence: 91%
“…These results indicates that the failure to detect the investigated fusion transcripts in normal GTEx samples is not due to differences in sequencing power between the cohorts, and that these fusion transcripts are specifically present in TGCT and not in normal tissue of the testis. This is in accordance with previously published experimental RT-PCR data (14), although then from relatively few samples.…”
Section: Tgct Fusion Transcripts Are Malignancy Specific and Not Detesupporting
confidence: 93%
See 2 more Smart Citations
“…Recently, it was shown that this technique could also be used to phase variants separated by up to 200 Kb (Regan et al 2015), which has already been applied to fusion transcript detection (Hoff et al 2016) or to phase deletions into haplotypes (Boettger et al 2016). Here, we have developed new ddPCR assays to genotype quickly and reliably human polymorphic inversions flanked by large IRs, and thanks to the genotype data we demonstrate that most of these inversions are recurrent and that inversion alleles are associated to gene expression changes.…”
Section: Introductionmentioning
confidence: 92%